Determinants of mental health status using depression anxiety stress scales during the COVID-19 pandemic: a systematic review - Riska Nabila; Rizma Adlia Syakurah; Rosyila Rosyila (Intelektual Pustaka Media Utama, 2022)
Coronavirus disease 2019 (COVID-19) is not only being a public physical health emergency, but also affecting global mental health, as evidenced by worldwide panic purchases, independent quarantine, and social distancing. Therefore, it is important to concern how a pandemic might affect one's mental state. The aim of this review was to determine mental health status in the community during COVID-19 pandemic using the depression anxiety stress scales (DASS) self-assessment. A comprehensive and systematic literature search published from January-May 2020 through electronic databases Pubmed, ScienceDirect, and Google Scholar was conducted based on guidelines from Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). This study used a self-report tool DASS to assess depression, anxiety, and stress. Seven studies with a total of 15.020 participants that were published in 2020 were included in the analysis. The characteristics that were chosen to determine the mental health status (depression, anxiety, and stress) were age, sex, level of education, and marital status. Findings from this review showed that sociodemographic characteristics (age, sex, marital status, education level) contributed to mental health status (depression, anxiety, and stress).